Upcycling of plastics recovered from enhanced landfill mining through pyrolysis. - Canopoli, Luisa (Cranfield University, 2020)
Since 1950 the global plastics production increased at a compound annual growth rate (CAGR) of about 8.5 % and it is expected to grow in the next 5 years at a CAGR of about 4 %. The estimated amount of plastics that ended up in landfill and natural environment in the past 70 years is 4.9 billion tonnes. Most of this comprises of thermoplastics which can be potentially recycled and reintroduced in the new circular plastic economy reducing the use of virgin fossil resources. To achieve this, more information is needed on recovered plastics physico-chemical characteristics and their suitability for conventional recycling processes. Due to the expected contamination and degradation of excavated plastics, potential upcycling routes need to be explored to produce marketable products. The plastic recycling, fresh waste or excavated, needs to fit into the circular economy strategy which aims to maximise service life and minimise waste. In the case of recovered plastics, the starting material is unused and must be renovated to become useful again. Between common recycling routes for fresh plastic waste, chemical recycling was found in line with the circular economy concept. Specifically, the pyrolysis method leads to the production of chemical compounds that can be used in the plastic industry. This PhD investigates the feasibility of producing valuable products from the pyrolysis of excavated plastics from municipal solid waste (MSW) landfill. Firstly, the physico-chemical characteristics of genuine plastic from landfills were analysed. The chemical and mechanical properties of buried plastics were hypothesised to be affected by the chemical, biochemical and physical parameters within a landfill environment. Secondly, the potential valuable products from the pyrolysis of recovered plastics were investigated. Polyethylene and polypropylene represented 64 wt% of total recovered plastics. The samples with storage of more than 10 years in landfill showed a general greater extent of degradation compared to newer samples. The pyrolysis of excavated plastics at 500°C and 650°C produced the highest level of hydrocarbons and most of the pyrolysis products fitted within the naphtha range (C6-C10) which has a high potential to be used in the petrochemical cluster. The findings from this PhD bring to the attention that buried plastics have hidden potential. These plastics have, in the past, been considered useless by virtue of being landfilled and are potentially harmful to the environment and ecosystem long-term in closed landfill sites. This work demonstrates the potential of recovering value from excavated plastics as part of an enhanced landfill mining project, reducing the need for virgin fossil fuel, preventing long-term pollutants release and producing valuable and useful products.
Keywords: Recycling; waste; circular economy; excavated plastic; secondary raw material; physio-chemical characteristics